2019
DOI: 10.1002/cpe.5413
|View full text |Cite
|
Sign up to set email alerts
|

Effective data placement for scientific workflows in mobile edge computing using genetic particle swarm optimization

Abstract: Mobile edge computing (MEC) necessitates cost-effective deployment for executing scientific workflows with different tasks and datasets, which provides computing, storage and network control at the network edge. However, the execution of scientific workflows in MEC results in heavy costs of data placement including data transmission and data storage. Although there are solutions for data placement in traditional cloud computing, they cannot effectively respond to the latency-sensitive property of scientific wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…A computing algorithm based on genetic algorithm to allocate computing resources was presented, and the results showed that the algorithm could minimize the energy consumption of user equipment [30]. In [31], Chen et al studied the data placement strategy of the workflow in MEC, and adopted a method based on genetic algorithm particle swarm optimization, and the final result shows that this method can effectively reduce the data placement cost of MEC.…”
Section: Resource Allocationmentioning
confidence: 99%
“…A computing algorithm based on genetic algorithm to allocate computing resources was presented, and the results showed that the algorithm could minimize the energy consumption of user equipment [30]. In [31], Chen et al studied the data placement strategy of the workflow in MEC, and adopted a method based on genetic algorithm particle swarm optimization, and the final result shows that this method can effectively reduce the data placement cost of MEC.…”
Section: Resource Allocationmentioning
confidence: 99%
“…The applications, services, application programming interface (API) and model-based workload have been implemented in [21][22][23][24][25][26][27]. The virtual machines, container and serverless aware resources are offered during workload execution in the system.…”
Section: Related Workmentioning
confidence: 99%
“…GAPSO [26] combines the best characteristics of the Genetic Algorithm (GA) and Particle Swarm Optimization (PSO) to distribute accordingly the data that are required from each edge node that participates in a scientific workflow. In particular, GA's crossover and mutation functions are integrated into PSO, whose ability to quickly converge to a solution is exploited.…”
Section: High Level Descriptionmentioning
confidence: 99%